Assessment of Colleges of Education Students’ Utilization of Web-based Tools f or Learning in Ilorin Metropolis - ASIYANBOLA, Caleb’; NUHU, Kehinde Muritala; ALASAN, Ndaceko Joel; TAIWO, Simeon Ayoola’ (International Journal of Educational Management, 2025)
Utilization of web-based tools for learning is one of the factors that can motivate and encourage students to learn as they become more independent and responsible for their learning. However, not many students in colleges of education have embraced the utilization of web-based tools for learning, especially in K wara State. This study, therefore, assessed the utilization of web-based tools for learning among colleges of education students in llorin Metropolis. A descriptive survey research design was adopted for this study, with sample purposively drawn from two colleges of education in I lorin. A researcher-designed questionnaire titled "Assessment of Colleges of Education Students’ Utilization of Web-based Tools for Learning in llorin Metropolis was used to gather data. Frequency counts and percentages were used to answer the research questions, while the two formulated research hypotheses were tested using t test at 0.05 level of significance. The findings of the study showed that there was no significant difference in the level of utilization of web-based tools for learning among Colleges of Education based on gender and school proprietorship. Based on the f indings of the study, it was recommended that the school administrators should ensure that seminars, workshops and conferences are organized in colleges of education to sensitize the students on the advantages of using web-based tools for learning.